Operating system concepts - Silberschatz, Abraham (J. Wiley & Sons, 2013)
Bibliography: 904 - 907; Introduction; Operating-System Structures; Processes; Threads; Process Synchronization; CPU Scheduling; Deadlocks; Main Memory; Mass-Storage Structure; File-System Interface; File-System Implementation; ...